A STUDY OF STUDENT’S ANXIETY IN SPEAKING SKILL - Amir Hamzah; Dhaniel Prasetyo Irianto (LPPM IAI Nazhatut Thullab, 2020)
Abstract: As we know English Language is one of the official languages of the United Nations and International languages become the most important soft skill to continue and to be taught in order to create a habit of using English, unfortunatelly Indonesia used English as foreign language not as second language this condtions makes speakers especially in speaking sometimeshas an anxiety to communicate and interact each other, one of case is college students, as students they certainly need to learn English as an academic language. but most of them are often nervous to pronounce English because they think English is one of the difficult languages. This study aims to describe about the elements cause students’anxiety in speaking skill and the students strategies to cope the anxiety in speaking skill at STIKes Ngudia Husada Madura in Medical Record Student of second semester in academic year 2019-2020 as participants. There are 21 students as participants researcher take by purposive sampling. Researcher also take 3 students in class of Medical Record. Descriptive Qualitative was used in this study. The data were through structured Interviews and classroom observations. The data were describe by interview transcripts. The result of this study describe three elementss that cause students’ anxiety in speaking English. The first is Self Perception of students that always feel English is difficulty to Learn and speak. The second elements is Class Condition of Performance make students got anxiety when they speak in front of their friends and lecture. The third is students’ Anxiety in speaking English is Fear of Making Mistakes. The result of this study also found there are three strategies that students used to cope the anxiety in speaking English. The first is Preparation, eight students did preparation always felt better before speaking English. The second is Positive thinking, seven participants did positive thinking can cope the anxiety in speaking English. The last is Relaxation, there five students take this strategie if students feel anxiety and failed speaking English. Keywords: Anxiety, Speaking Skill